Evaluating the application value of NGS-based PGT-A by screening cryopreserved MDA products of embryos from PGT-M cycles with known transfer outcomes - Shen, Xiaoting; Chen, Dongjia; Ding, Chenhui; Xu, Yan; Fu, Yu; Cai, Bing; Wang, Yali; Wang, Jing; Li, Rong; Guo, Jing; Pan, Jiafu; Zhang, Han; et al. (Journal of assisted reproduction and genetics, 2022)
Purpose To determine the application value of next-generation sequencing (NGS)-based preimplantation genetic testing for aneuploidies (PGT-A). Methods We conducted a retrospective case–control study on a cohort of frozen-thawed embryo transfer (FET) cycles following preimplantation genetic testing for monogenic disorders (PGT-M) between 2014 and 2017. Cycles that produced live births or early miscarriages were divided into live birth group ( n = 76) or miscarriage group ( n = 19), respectively. The NGS-based aneuploidy screening was performed on the multiple displacement amplification (MDA) products of the embryonic trophectoderm biopsy samples that were cryopreserved following PGT-M. Results In the live birth group, 75% (57/76) embryos were euploid and 14.5% (11/76) were aneuploid. The remaining 10.5% (8/76) embryos were NGS-classified mosaic with the high- (≥ 50%) and low-level (< 50%) mosaicism rates at 7.9% (6/76) and 2.6% (2/76), respectively. In the miscarriage group, only 23.5% (4/17) embryos were aneuploid, while 58.8% (10/17) were euploid and 17.6% (3/17) were NGS-classified mosaic with the high- and low-level mosaicism rates at 11.8% (2/17) and 5.9% (1/17), respectively. For live birth and miscarriage groups, the transferable rate was 82.9% (63/76) and 70.6% (12/17), respectively, whereas the untransferable rate was 17.1% (13/76) and 29.4% (5/17), respectively. Conclusion The application of NGS-based PGT-A remains questionable, as it may cause at least one in six embryos with reproductive potential to be discarded and prevent miscarriage in less than one in three embryos in single-gene disease carriers.